A clean innovation comparison between carbon tax and cap-and-trade system. (May 2020) - Chen, You-hua; Wang, Chan; Nie, Pu-yan; Chen, Zi-rui
Abstract: Both carbon tax and cap-and-trade systems are widely applied to reduce emission. This article compares the clean innovation effects of carbon tax with cap-and-trade systems by a static optimal model. Firstly, both cap-and-trade system and carbon tax stimulates clean innovation and reduce emission. Secondly, cap-and-trade system is more efficient to reduce emission and to promote clean innovation than carbon tax. Finally, firms undertake a loss under carbon tax, while the effects of cap-and-trade system on firms' profits are uncertain, which depends on the carbon cap. In summary, this article supports cap-and-trade system to cope with global climate change, but the regulator should choose the suitable emission cap and carbon trading price to guarantee the efficiency of cap-and-trade system. So, different purposes match with different carbon emission tax policies. Highlights: Both cap-and-trade system and carbon tax stimulate clean innovation. The effects of cap-and-trade system on firms' profits are uncertain. Cap-and-trade system has higher efficiency than carbon taxes on global climate change control. This article further develops the innovative theory under both carbon tax and cap-and-trade systems.